The Effect of Curcuma and Garcinia Peel on Rat PPARα Gene Expression Induced by High-Fat Diet - Jasaputra, Diana Krisanti; Yumilia, Hoo; Gunadi, Julia Windi; Lesmana, Ronny; Permadi, Andieni Faqhira (Global Medical & Health Communication (GMHC), 2023)
High levels of fat in the blood are a risk factor for nonalcoholic steatohepatitis liver disease. Indonesian medicinal plants that can decrease blood fat levels are turmeric and mangosteen peel. One of the mechanisms of blood fat-lowering drugs is to increase the expression of the PPARα gene. The purpose of this study was to assess the effect of turmeric and mangosteen peel on the expression of the PPARα gene in the rat liver induced by a high-fat diet. This research was conducted at Maranatha Biomedical Research Laboratory in February–October 2021, using male Wistar rats that were divided into 5 groups (n=5): negative control groups (no treatment), positive control groups (high-fat diet), turmeric, mangosteen, and fenofibrate groups, that was given high-fat diet continued by ethanol extract of turmeric, ethanol extract of mangosteen peel, and fenofibrate. At the end of the study, the animals were terminated, and the liver was extracted for RNA extraction and semi-quantitative PCR. The results showed that there was an increase in PPARα gene expression in the turmeric group and fenofibrate group, which were significantly different from the positive control group that received a high-fat diet (p<0.05) and between the fenofibrate group compared to negative controls that received standard chow diet (p<0.05). In conclusion, turmeric and fenofibrate are suggested to increase the expression of the PPARα gene in the liver induced by a high-fat diet.